1996
DOI: 10.1016/s0194-5998(96)70145-6
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Cholesteatoma: An Individualized, Single‐Stage Approach

Abstract: We report our experience with a one-stage surgery for pediatric cholesteatoma in 216 ears. Our technique is based on three main principles: (1) the surgery is individualized; (2) the goal of surgery is to completely remove cholesteatoma and related disease in one operation; and (3) the reconstruction is performed to provide both good hearing and a dry, trouble-free ear. The incidence of recidivism was 10.2%, and the rate achieved was 13.3% at 5 years and 24% at 10 years. Canal wall down surgery was the predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 23 publications
5
28
2
Order By: Relevance
“…In this series, 79% of children with cholesteatoma were initially managed using an ICW approach, with only 4.5% (10/ 221) of these cases eventually requiring a CWD procedure. There was an overall recurrence rate of 16%, with an ICW rate of 17% and a CWD rate of 12%, which is consistent with the literature [2,[9][10][11][12][13][14] ( Table 2).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this series, 79% of children with cholesteatoma were initially managed using an ICW approach, with only 4.5% (10/ 221) of these cases eventually requiring a CWD procedure. There was an overall recurrence rate of 16%, with an ICW rate of 17% and a CWD rate of 12%, which is consistent with the literature [2,[9][10][11][12][13][14] ( Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…Regardless of technique, recurrence rates for adults and children are between 7 and 57% [2,[9][10][11][12][13][14]. However, Tos et al [15] reported results on 740 patients and found no differences in recurrence rates between the two approaches and fewer complications with ICW.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, performing a second, third or even fourth look can be an unnecessary hardship for both the child and the family. This observation is supported by Parisier et al [1996], who proposed that cholesteatomas can be exenterated safely in one stage using either the CWU or CWD techniques. Additionally, due to the late recidivism of residual cholesteatomas (mean detection time 5 years, maximum 11.6 years), it may be better to wait for the disease to reappear instead of taking a second look at 6-18 months after surgery in all children.…”
Section: Discussionmentioning
confidence: 60%
“…However, these techniques are not routinely performed and canal wall-up (CWU) tympanoplasties for middle ear cholesteatoma usually require second-look surgery to rule out the presence of residual cholesteatoma, observed in 6%-57% of patients in large series. 4,5 Any reliable noninvasive method of detecting residual cholesteatomas could allow the avoidance of second-look surgery in patients with no hearing loss after the first surgery.…”
mentioning
confidence: 99%